Force and vibration analysis in biomechanical preparation of root canals using reciprocating endodontic file system: In vitro study. (January 2022) - Thakur, Vinod Singh; Kankar, Pavan Kumar; Parey, Anand; Jain, Arpit; Jain, Prashant Kumar
The shaping and cleaning of the root canal are very important in root canal treatment. The excessive force and vibration during biomechanical preparation of the root canal may result in failure of the endodontic file. In this study, force and vibration analysis was carried out during root canal preparation. The samples of human extracted (premolar) teeth were provided by the College of Dental Science and Hospital. Endodontic instruments for reciprocating motion, such as the WaveOne Gold file system, had been used for root canal preparation. Force and vibration signals were recorded by dynamometer and accelerometer, respectively. The acquired signals were denoised using the db4 (SWT denoising 1-D) wavelet. Four levels of decomposition were carried out for each signal. The signal denoising technique was used to remove unwanted noise from the acquired signal. FESEM analysis was used to visualize the levels of severity of endodontic files during the cleaning and shaping of the root canal. In most of the cases, the failure occurred due to the improper use of the root canal instrumentation. The optimum amount of force was used to avoid the file failure and provided the proper instrumentation. The curve fitting regression model was used to find the interdependency between force and vibration.